Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Hello again! Can you people please help me in this math question?
https://imgur.com/a/3DLLG, here are the questions, I'm currently practicing for UPCAT and these are from a free test I found on the internet, thank you!
4 Answers
- JeremyLv 64 years agoFavorite Answer
(a) x/(x^2 + 6x + 8) = √576/(x + 2).
x/[(x + 2) * (x + 4)] = 24/(x + 2) <--- (*)Set: x + 2 ≠ 0 ---> x ≠ -2, and x + 4 ≠ 0 ---> x ≠ -4.
Multiply both sides by [(x + 2) * (x + 4)].
[(x + 2) * (x + 4)] * x/[(x + 2) * (x + 4)] = [(x + 2) * (x + 4)] * 24/(x + 2).
---> x = 24(x + 4).
x = 24x + 96.
x - 24x = 96.
-23x = 96.
x = -96/23 (Feasible solution, according to the solution set of the equation).
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
(b) 2x^2 + 7x + 6 = 0 <--- Use the quadratic formula in order to find the roots.
x = [-7 ± √(49 - 48)]/4 = (-7 ± 1)/4.
Either: x = (-7 - 1)/4 = -8/4 = -2 (Answer).
Or: x = (-7 + 1)/4 = -6/4 = -3/2 (Answer).
The only correct choice in your list is a) (Answer).
- Paul Jean PierreLv 54 years ago
x / (x² + 6x + 8) = √(576) / (x+2)
x / [(x+4)(x+2)] = 24 / (x+2)
x / (x+4) = 24
x = 24(x+4)
x = 24x + 96
23x = -96
x = -96/23
119.
2x² + 7x + 6 = 0
(2x+3)(x+2) = 0
x = -3/2 or -2
- 戇戇居士Lv 74 years ago
117.
x / (x² + 6x + 8) = √576 / (x + 2)
x / [(x + 2) (x + 4)] = 24 / (x + 2)
x + 2 ≠ 0 , then,
x / (x + 4) = 24
x = 24 (x + 4)
x = 24x + 96
-23x = 96
x = -96/23
The answer: d. -96/23
====
119.
2x² + 7x + 6 = 0
(2x + 3)(x + 2) = 0
2x + 3 = 0 or x + 2 = 0
x = -3/2 or x = -2
- icemanLv 74 years ago
117)
x/(x^2 + 6x + 8) = √576/(x + 2)
x/(x^2 + 6x + 8) = 24/(x + 2)
24x^2 + 144x + 192 = x^2 + 2x
23x^2 + 142x + 192 = 0
(x + 2)(23x + 96) = 0
x = -2, -96/23 => reject x = -2 since it makes the denominator zero thus not in the domain
x = -96/23
d) => answer
118)
2x^2 + 7x + 6 = 0 => use the rational root theorem:
factors of 6 => ± (1, 2, 3, 6)
factors of 2 => ± (1, 2)
thus the possible rational roots are ± (1, 1/2, 2, 3/2, 3, 6) by inspection we find x = -2 is a root:
2(-2)^2 - 14 + 6 = 8 - 14 + 6 = 0 and we can find the other root by inspection or using synthetic division now let's verify by factoring:
2x^2 + 7x + 6 = 0
2x^2 + 4x + 3x + 6 = 0
2x(x + 2) + 3(x + 2) = 0
(x + 2)(2x + 3) = 0
x = -2, -3/2
a) => correct choice